Processing box

By using resin particles and silica particles of specific structures in the surface layer of the treatment box, the problems of toner accumulation and aggregation blocks in high-temperature and high-humidity environments are solved, and the stability of image quality and service life is achieved.

CN114280904BActive Publication Date: 2024-12-13CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111143545.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-28
Filing Date
2021-09-28
Publication Date
2024-12-13
Estimated Expiration
2041-09-28

AI Technical Summary

Technical Problem

When using an electrophotographic device in a high temperature and high humidity environment, the toner between the developing roller of the processing box and the adjustment member is prone to accumulate, resulting in the formation of agglomeration blocks, and the problem of transverse white stripes occurs during use.

Method used

A removable treatment box is designed, including a conductive substrate, an elastic layer and a surface layer, which consists of a binder resin, a first resin particle and a second resin particle, and has a specific elastic coefficient and a convex structure. The external additive is silica particles having a length diameter of 40nm or more and 400nm or less, and is used to prevent the accumulation of toner and reduce adhesion.

Benefits of technology

Effectively prevent the accumulation of toner between the developing roller and the adjustment member, reduce the formation of agglomerates, and ensure the stability of image quality and service life when used in high-temperature and high-humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114280904B_ABST
    Figure CN114280904B_ABST
Patent Text Reader

Abstract

The present invention relates to a process box. A process box includes a toner, a regulating member, and a developing roller, the developing roller includes a conductive substrate, an elastic layer, and a surface layer, the surface layer includes a binder resin, first resin particles with an elastic coefficient of 100 to 10,000 MPa, and second resin particles with an elastic coefficient of 2 to 50 MPa, and the outer surface of the surface layer has a first convex portion and a second convex portion that is 5.0 μm or more lower than the first convex portion and the average value of the maximum height is 6 to 18 μm. The toner includes toner particles and an external additive A that is a silica particle with a long diameter of 40 to 400 nm, the surface coverage of the external additive A to the toner particles is 3.0% or more, and the dispersion evaluation index D of the external additive A is 2.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a process cartridge. Background Art

[0002] In an electrophotographic image forming apparatus (hereinafter also referred to as an "electrophotographic apparatus"), an electrophotographic photosensitive member serving as an image bearing member is charged by a charging device, and an electrostatic latent image is formed by laser. Subsequently, the toner in the developer container is applied to the developing member by a toner supply roller and a toner regulating member, and development is performed with the toner due to contact or proximity between the image bearing member and the developing member. Thereafter, the toner on the image bearing member is transferred to recording paper by a transfer device and fixed by heat and pressure, and the toner remaining on the image bearing member is removed by a cleaning member.

[0003] Such electrophotographic apparatuses are required to have higher image quality and durability and faster printing speed than before. As a result, electrophotographic members and toners are required to have higher performance.

[0004] In addition, in recent years, electrophotographic apparatuses have been used in various fields, and have also been used in harsh high-temperature and high-humidity environments, which particularly aggravate toner degradation and member contamination. An electrophotographic member or toner that stably maintains high image quality and durability even in such harsh environments is desired.

[0005] Japanese Patent Application Laid-Open No. 2009-237042 discloses a developing roller, which includes acrylic particles and urethane particles having an average particle diameter smaller than that of the acrylic particles in a surface layer of the developing roller for the purpose of preventing toner from being melt-adhered to the developing roller. For the developing roller disclosed in Japanese Patent Application Laid-Open No. 2009-237042, the purpose is to suppress the toner from being melt-adhered to the developing roller by reducing the stress caused by the friction between the developing roller and the toner regulating member and applied to the toner on the developing roller.

[0006] Japanese Patent Application Laid-Open No. 2007-171666 proposes a method in which inorganic fine particles having a large particle size of about several hundred nanometers, in particular, sol-gel silica particles having a narrow particle size distribution are added. Accordingly, a so-called spacer effect is produced, a developing roller, a regulating member, etc. are prevented from directly contacting the toner, and stress is reduced. As a result, damage to the toner is reduced and a long service life of the toner is achieved.

[0007] As a result of the inventors' studies, it was found that the above case has a problem of horizontal streaks when a process cartridge (hereinafter also referred to as "cartridge") is left for a long period of time during use in a high-temperature and high-humidity environment.

[0008] The reason why horizontal streaks are generated when the cartridge is left for a long time during use is presumed as follows. When use is stopped, toner accumulation occurs between the developing roller and the regulating member. At this time, if the amount of toner accumulated between the developing roller and the regulating member is large, the toner is in a state of being crushed by the pressure between the regulating member and the developing roller. If the toner in this state is left in a high temperature and high humidity environment for a long time, the toner becomes a coagulated mass due to, for example, seeping out from the inside of the toner and melting and adhering to the developing roller and the regulating member. If the cartridge is started to be used in this state, horizontal white streaks are generated because the toner is not applied in the longitudinal direction where the coagulated mass is melted and adhered. Summary of the invention

[0009] The present disclosure provides a process cartridge capable of producing high-quality images even when the speed is increased, even when the service life is increased, and even after being left for a long period of time during use of the process cartridge in a high-temperature and high-humidity environment.

[0010] The present inventors have conducted intensive studies to solve the above problems. As a result, they have found that the above problems can be solved by using a process cartridge including a developing roller and a toner described later.

[0011] A process cartridge detachably mounted to a main body of an electronic photographic apparatus, comprising a toner, a developing roller, and a regulating member, wherein the developing roller comprises a conductive substrate, an elastic layer on the conductive substrate, and a surface layer on the elastic layer, the surface layer comprising a binder resin, first resin particles, and second resin particles, the surface layer having an outer surface having a first convex portion and a second convex portion present in a region excluding the first convex portion and having a height lower than that of the first convex portion by 5.0 μm or more, the first convex portion originating from the first resin particles, the second convex portion originating from the second resin particles, the elastic modulus of the first resin particles being 100 MPa or more and 10,000 MPa or less, and the first resin particles having a The elastic coefficient is measured in a cross section in the thickness direction of the surface layer, the elastic coefficient of the second resin particles is greater than or equal to 2 MPa and less than or equal to 50 MPa, the elastic coefficient of the second resin particles is measured in a cross section in the thickness direction of the surface layer, the average value of the maximum height Rz of the outer surface is greater than or equal to 6 μm and less than or equal to 18 μm, the colorant includes colorant particles and an external additive A dispersed on the surface of the colorant particles and covering the surface of the colorant particles, the external additive A is a silica particle having a major diameter of greater than or equal to 400 nm and less than or equal to 400 nm, the coverage rate of the external additive A on the surface of the colorant particles is greater than or equal to 3.0%, and the dispersion evaluation index D of the external additive A is less than or equal to 2.0.

[0012] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a schematic diagram showing an example of an electrophotographic image forming apparatus according to the present disclosure.

[0014] Figure 2 is a schematic diagram illustrating an example of a developing roller according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0015] Hereinafter, the present invention will be described in detail.

[0016] The present invention relates to a process cartridge that is detachably mounted to a main body of an electronic photographic apparatus. The process cartridge includes a toner, a developing roller, and a regulating member, wherein the developing roller includes a conductive substrate, an elastic layer on the conductive substrate, and a surface layer on the elastic layer, the surface layer includes a binder resin, first resin particles, and second resin particles, the outer surface of the surface layer has a first convex portion and a second convex portion that exists in a region that does not include the first convex portion and has a height that is 5.0 μm or more lower than the height of the first convex portion, the first convex portion is derived from the first resin particle, the second convex portion is derived from the second resin particle, and the elastic coefficient of the first resin particle measured in a cross section in the thickness direction of the surface layer is 10 The present invention relates to a toner having an elastic modulus of at least 0 MPa and at most 10,000 MPa, an elastic modulus of the second resin particles measured in a cross section in a thickness direction of the surface layer is at least 2 MPa and at most 50 MPa, an average value of a maximum height Rz of an outer surface is at least 6 μm and at most 18 μm, the colorant comprises toner particles and an external additive A, the external additive A is a silica particle having a major diameter of at least 40 nm and at most 400 nm, a coverage rate of the external additive A on the surface of the toner particles is at least 3.0%, and a dispersion evaluation index D of the external additive A is at most 2.0.

[0017] The reason why horizontal streaks are generated when the cartridge is left for a long time during use is presumed as follows. When use is stopped, toner accumulation occurs between the developing roller and the regulating member. At this time, if the amount of toner accumulated between the developing roller and the regulating member is large, the toner is in a state of being crushed by the pressure between the regulating member and the developing roller. If the toner in this state is left in a high temperature and high humidity environment for a long time, the toner becomes a coagulated mass due to, for example, seeping out from the inside of the toner and melting and adhering to the developing roller and the regulating member. If the cartridge is started to be used in this state, horizontal white streaks are generated because the toner is not applied in the longitudinal direction where the coagulated mass is melted and adhered.

[0018] On the other hand, in the present disclosure, it is presumed that the above-mentioned problem is solved according to the mechanism described later. It is presumed that since the elastic coefficient of the first resin particles is 100 MPa or more and 10,000 MPa or less, and therefore has high hardness, when the operation of the box stops, a force is generated to push out the toner accumulated between the developing roller and the regulating member. If the elastic coefficient is less than 100 MPa, the hardness is insufficient, and the first resin particles are easily deformed by the pressure from the regulating member, so that the thrust is weakened. If the elastic coefficient is greater than 10,000 MPa, it is difficult to exert the effect of the present invention throughout the durability period due to increased damage to the toner. The average elastic coefficient E1 described later is more preferably 100 MPa or more and 7,500 MPa or less, and E1 is further preferably 100 MPa or more and 2,000 MPa or less. In the present disclosure, since the height difference between the convex portion derived from the first resin particles and the convex portion derived from the second resin particles is 5 μm or more, the first resin particles having high hardness can effectively transmit the thrust to the toner. If the difference is less than 5 μm, the thrust is weakened because the toner is larger than the first resin particles. In addition, the elastic coefficient of the second resin particles, which have low convexities and correspond to the portion where the toner is introduced into the developing roller, is 2.0 MPa or more and 50 MPa or less, and the convexities are soft, so that the toner further sinks relative to the first resin particles due to the pressure from the regulating member. As a result, the thrust of the first resin particles is more easily transmitted to the toner. If the elastic coefficient is less than 2.0 MPa, it is difficult to exert the effect of the present disclosure throughout the durability period, and if the elastic coefficient is greater than 50 MPa, the thrust of the first resin particles is not effectively transmitted to the toner due to the low degree of sinking caused by the pressure from the regulating member. The average value of the maximum height Rz is a parameter representing the height and frequency of the higher convexities among the multiple convexities present on the outer surface. The average value of Rz is 6 μm or more and 18 μm or less so that the first convexities present on the outer surface have a height and frequency sufficient to protrude the head outside the toner layer applied to the developing roller for pushing out. If the average value of Rz is less than 6 μm, the height and frequency are insufficient to be derived, and if the average value of Rz is greater than 18 μm, since the frequency of particles having high hardness is high, it is difficult to exert the effect of the present disclosure throughout the latter half of the durability period due to damage to the toner. The average value of Rz is more preferably 8 μm or more and 16 μm or less.

[0019] The dispersion evaluation index D of the large particle size external additive contained in the colorant and having a long diameter of 40 nm or more and 400 nm or less is controlled to be less than 2.0. As a result, the spacer effect of the large particle size external additive makes it possible to prevent the colorant from being deformed due to the pressure between the developing roller and the regulating member, and the thrust of the first resin particles is more easily transmitted to the colorant. Since the dispersion evaluation index D is within the above range, the adhesion reduction effect caused by the large particle size external additive can be more effectively exerted, thereby eliminating the accumulation of the colorant between the developing roller and the regulating member. The dispersion evaluation index D of the external additive A is more preferably 0.5 or more and 1.20 or less. If the long diameter of the external additive A is less than 40 nm, due to the low spacer effect, the colorant cannot be prevented from being deformed due to the pressure between the developing roller and the regulating member, and the adhesion reduction effect is low. If the long diameter is greater than 400 nm, it is difficult to control the dispersion evaluation index D within the range according to the present disclosure. The average long diameter Da described later is more preferably 40 nm or more and 300 nm or less. If the dispersion evaluation index is greater than 2.0, due to the serious uneven distribution of the external additive A on the colorant surface, the colorant cannot be prevented from being deformed due to the pressure between the developing roller and the regulating member, and the adhesion reduction effect is low. The dispersion evaluation index is more preferably 0.5 or more and 1.2 or less. Since the dispersion evaluation index is 0.5 or more, the entanglement of the colorants due to the external additive A is reduced, the colorant is easily disentangled by the thrust of the first resin particles, and the accumulation of the colorant due to the cessation of the use of the box is not easy to occur. The dispersion of the external additive A can be controlled by the addition amount of the external additive A and the external addition conditions. The surface coverage of the external additive A to the colorant particles is 3.0% or more. If the surface coverage is less than 3.0%, from the perspective of preventing the colorant from being deformed due to the pressure between the developing roller and the regulating member and reducing the adhesion, the effect of the present disclosure cannot be exerted. The surface coverage is more preferably 5.0% or more and 30% or less. The surface coverage may be 30% or less, because the dispersion degree can be easily controlled within the range according to the present disclosure, and the effects of the present disclosure can be more easily exerted. The surface coverage of the external additive A can be controlled by the major diameter of the external additive A and the amount of the external additive A added.

[0020] The toner according to the present disclosure may contain silica particles used as an external additive B and having a long diameter of 5 nm or more and less than 40 nm, wherein the coverage of the toner particles by the external additive B is 62% or more and 100% or less. A coverage of 62% or more improves the fluidity of the toner, the toner is easily untied by the thrust of the first resin particles, and the accumulation of the toner due to the discontinuation of the cartridge is not likely to occur. The coverage of the external additive B on the toner surface can be controlled by the addition amount of the external additive B and the external addition conditions.

[0021] The total fixation rate of the external additive A and the external additive B of the toner according to the present disclosure is preferably 70% or more. Since the total fixation rate is 70% or more, the fluidity of the toner can be maintained in the second half of the durability period, and the effect of the present disclosure can be easily exerted throughout the second half of the durability period. The total fixation rate of the external additive A and the external additive B can be controlled by the addition amount of the external additive A and the external additive B and the external addition conditions.

[0022] In the present disclosure, the volume average diameter D1 of the first resin particles, the volume average diameter D2 of the second resin particles, and the volume average diameter Dt of the toner may satisfy the relationship represented by the following formula (a).

[0023] (D1-D2)-Dt>0 (a)

[0024] Since the relationship represented by formula (a) is satisfied, the first resin particles are higher than the surface of the toner applied to the second resin particles, and the pushing force of the first resin particles having high hardness is more easily transmitted to the toner.

[0025] The volume average diameter D2 of the second resin particles and the average major diameter Da of the external additive A may satisfy the relationship represented by the following formula (b).

[0026] D2 / Da≤40 (b)

[0027] Since satisfying the relationship represented by formula (b) enables the external additive A to enter the gaps between the second resin particles and enables the toner to be easily untangled, the effects of the present disclosure are more favorably exerted.

[0028] Hereinafter, embodiments according to the present disclosure will be described in detail.

[0029] The developing roller according to the present embodiment will be described in detail below.

[0030] Developing roller

[0031] As a schematic cross-sectional view in a direction perpendicular to the axial direction Figure 2 As shown in FIG. 1 , the developing roller 220 according to the present embodiment includes a conductive substrate 221, a conductive elastic layer 223 on the conductive substrate, and a surface layer 222 on the conductive elastic layer. The conductive elastic layer 223 may have at least one layer as appropriate. The surface layer 222 is a single layer.

[0032] Conductive substrate

[0033] The conductive substrate has the function of supporting the conductive elastic layer and the surface layer provided thereon. Examples of the material of the conductive substrate include metals such as iron, copper, aluminum, and nickel; and alloys containing these metals such as stainless steel, duralumin, brass, and bronze. These may be used alone, or at least two may be used in combination. For the purpose of providing scratch resistance, the substrate surface may be electroplated within a range that does not impair conductivity. In addition, a substrate in which a conductive surface is provided by covering the surface of a resin substrate with a metal or a substrate produced from a conductive resin composition may be used.

[0034] Conductive elastic layer

[0035] The conductive elastic layer may be a solid body or a foamed body. The conductive elastic layer may be composed of a single layer or multiple layers. The elastic modulus of the conductive elastic layer is preferably 0.5 MPa (0.5×10 6 Pa) and above 10MPa (10×10 6 Pa) or less. Examples of materials for such conductive elastic layers include natural rubber, isoprene rubber, styrene rubber, butyl rubber, butadiene rubber, fluororubber, polyurethane rubber, and silicone rubber. These can be used alone, or at least two can be used in combination. Among them, silicone rubber can be used because it has a low elastic modulus.

[0036] The conductive elastic layer can contain a conductive agent, a non-conductive filler, and other additive components required for various shaping, such as a cross-linking agent, a catalyst, and a dispersion promoter, according to the required function of the developer roller. For the conductive agent, various conductive metals or their alloys, conductive metal oxides, fine particles of insulating materials covered with these, electronic conductive agents, and ionic conductive agents, etc. can be used. These powdery or fibrous conductive agents can be used alone, or at least two can be used in combination. Among them, carbon black used as an electronic conductive agent can be used because it is easy to control conductivity and economy. Examples of non-conductive fillers include diatomaceous earth, quartz powder, dry silica, wet silica, titanium oxide, zinc oxide, aluminosilicate, calcium carbonate, zirconium silicate, aluminum silicate, talc, aluminum oxide, and iron oxide. These can be used alone, or at least two can be used in combination.

[0037] The volume resistivity of the conductive elastic layer is preferably 1.0×10 4 to 1.0×10 10 Ω·cm. When the volume resistivity of the conductive elastic layer is within this range, it is easy to prevent the development electric field from fluctuating. The volume resistivity is more preferably 1.0×10 4 to 1.0×10 9 Ω·cm. The volume resistivity of the conductive elastic layer can be controlled by the content of the conductive agent in the conductive elastic layer.

[0038] The thickness of the conductive elastic layer is preferably 0.1 mm or more and 50.0 mm or less and more preferably 0.5 mm or more and 10.0 mm or less.

[0039] Examples of the method for forming the conductive elastic layer include a method in which the conductive elastic layer is formed on a substrate by heat-hardening with an appropriate temperature and time using various molding methods such as extrusion molding, press molding, injection molding, liquid injection molding, and casting molding. For example, the conductive elastic layer is accurately formed on the outer periphery of the substrate by injecting an unhardened material for forming the conductive elastic layer into a cylindrical mold in which the substrate is placed and heat-hardening.

[0040] Surface layer

[0041] The outer surface of the surface layer has a first convex portion and a second convex portion that is present in an area excluding the first convex portion and is 5.0 μm or more lower than the height of the first convex portion. The first convex portion is derived from the first resin particles, and the second convex portion is derived from the second resin particles. The elastic coefficient of the first resin particles measured in the cross section in the thickness direction of the surface layer is 100 MPa or more and 10,000 MPa or less. The elastic coefficient of the second resin particles measured in the cross section in the thickness direction of the surface layer is 2 MPa or more and 50 MPa or less. The average value of the maximum height Rz of the outer surface is 6 μm or more and 18 μm or less.

[0042] The peak vertex density SpD is preferably 5.0×10 3 (1 / mm 2 ) and above 5.0×10 4 (1 / mm 2 )the following.

[0043] In order to control the conductivity of the surface layer, a conductive agent may be mixed in the surface layer. Additives such as a surfactant may be mixed to control the releasability of the toner.

[0044] Furthermore, since the effect of pushing out the toner by the first resin particles is increased, the vicinity of the outer surface of the surface layer can have high hardness.

[0045] The layer thickness of the surface layer is preferably 4 μm or more and 100 μm or less. The layer thickness is the thickness at the portion where neither the first convex portion nor the second convex portion is provided. The thickness may include the first resin particles that do not form the first convex portion or the second resin particles that do not form the second convex portion. When the layer thickness is set to 4 μm or more, the first convex portion and the second convex portion that are respectively derived from the first resin particles and the second resin particles are easily formed, and the average value and SpD of Rz are easily set within the above range. The layer thickness may be set to 4 μm or more, because the influence of the elastic coefficient Eb of the surface layer matrix is ​​significant even when the hardness near the outer surface of the surface layer increases, and soft deformation of the surface layer is likely to occur. The layer thickness may be set to 100 μm or less, because soft deformation of the surface layer is likely to occur. The layer thickness is more preferably 6 μm or more and 30 μm or less.

[0046] Surface layer matrix

[0047] The surface layer matrix may include polyurethane as a binder. Cross-linked urethane resin is suitable for use as a binder due to excellent flexibility and strength.

[0048] Polyurethane is obtained by polyol, isocyanate and chain extender according to applicable needs. The example of polyol used as the material for forming polyurethane comprises polyether polyol, polyester polyol, polycarbonate polyol, polyolefin polyol and acrylic polyol and the mixture of these. The example of isocyanate used as the material for forming polyurethane comprises toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), toluidine diisocyanate (TODI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), tetramethyl xylylene diisocyanate (TMXDI) and cyclohexane diisocyanate and the mixture of these. Examples of chain extenders include difunctional low molecular weight diols such as ethylene glycol, 1,4-butanediol, and 3-methylpentanediol, trifunctional low molecular weight triols such as trimethylolpropane, and mixtures thereof. Alternatively, a prepolymer type isocyanate compound having an isocyanate group at the end and obtained by reacting the above various isocyanate compounds with the above various polyols in advance in a state where the isocyanate group is excessive can be used. For the isocyanate compound, a material produced by blocking the isocyanate group with various blocking agents such as MEK oxime can be used.

[0049] Regardless of which material is used, polyurethane can be obtained by reacting polyol with isocyanate by heating. In this aspect, when one or both of the polyol and the isocyanate have a branched structure and at least three functional groups, the resulting polyurethane is a cross-linked polyurethane.

[0050] The elastic coefficient Eb at a depth of 1 μm or more from the outer surface of the matrix measured by the method described later is preferably 10 MPa or more and 100 MPa or less. When the elastic coefficient Eb is set to 10 MPa or more, the effect of pushing out the toner by the first resin particles is easily exerted, wherein the first convex portion is formed by covering the first resin particles. The elastic coefficient Eb is set to 100 MPa or less so that the area in which the second resin particles exist can be softly deformed with the second resin particles. As a result, the toner further sinks relative to the first resin particles due to the pressure from the regulating member, and the thrust of the first resin particles can be more easily transmitted to the toner.

[0051] The elastic coefficient Eb of the surface layer matrix is ​​adjusted to the above range by the molecular structure of the resin, the interaction due to the addition of fine particles such as silica or carbon black, and the like.

[0052] The first convex part and the second convex part

[0053] The outer surface of the surface layer has a first convex portion and a second convex portion that exists in a region excluding the first convex portion and whose height is 5.0 μm or more lower than the height of the first convex portion. The first convex portion originates from the first resin particles described later, and the second convex portion originates from the second resin particles described later. The two convex portions that exist on the outer surface of the surface layer and have a height difference of 5.0 μm or more are confirmed by using the method described later, and the elastic coefficients of the particles constituting the two convex portions are measured by using the method described later. As a result, it is confirmed that the first convex portion and the second convex portion exist on the outer surface of the surface layer.

[0054] Average value of maximum height Rz

[0055] The average value of the maximum height Rz of the outer surface of the surface layer is 6 μm or more and 18 μm or less. The average value of the maximum height Rz is a value determined by the measurement method described later, and is the average value of multiple maximum heights Rz, and is therefore a parameter that can represent the height and frequency of the higher convex portion among the multiple convex portions present on the outer surface. In the present disclosure, since the first convex portion is higher than the second convex portion, the average value of Rz has a strong correlation with the height and frequency of the first convex portion. The average value of Rz is set to be 6 μm or more and 18 μm or less so that the first convex portion present on the outer surface has a height and frequency sufficient to protrude the head outside the toner layer applied to the developing roller for pushing out. If the average value of Rz is less than 6 μm, the height and frequency are insufficient to push out, and if the average value of Rz is greater than 18 μm, since the frequency of particles with high hardness is high, it is difficult to exert the effect of the present disclosure throughout the second half of the durability period due to damage to the toner. The average value of Rz is more preferably 6 μm or more and 18 μm or less.

[0056] As described above, the average value of Rz has a strong correlation with the height and frequency of the first convex portion, and is therefore mainly adjusted by the volume average particle diameter and the mixing amount of the raw material used to form the first resin particles. In addition, the protruding state of the first resin particles is also changed by the volume average particle diameter and the mixing amount of the raw material used to form the second resin particles and the layer thickness of the surface layer, and the average value of Rz is also adjusted. In this regard, the volume average particle diameter of the raw material resin particles is a median diameter based on the "laser diffraction-scattering method" by using a particle size distribution analyzer as shown in the examples described later.

[0057] Peak vertex density SpD

[0058] The peak vertex density SpD of the outer surface of the surface layer measured by the method described later is preferably 5.0×10 3 (1 / mm 2 ) and above 5.0×10 4 (1 / mm 2 ) or less. The peak vertex density SpD is a parameter indicating the number of convexities present per unit area, and when there are multiple convexities, it has a strong correlation with the frequency of small convexities. Therefore, SpD has a strong correlation with the frequency of the second convexity. SpD is set to 5.0×10 3 (1 / mm 2 ), that is, there are many second convex portions so that the pushing force of the first resin particles can be effectively transmitted to the toner due to the sinking of the second resin particles. Since the portion of the second resin particles into which the toner is introduced is not excessive relative to the first resin particles that push out the toner, SpD is set to 5.0×10 4 (1 / mm 2 )The following makes it easy to exert the effects of the present disclosure.

[0059] The SpD according to the present disclosure can be adjusted by the volume average particle size and the mixing amount of the first resin particles and the second resin particles described below. Since SpD has a strong correlation with the frequency of the relatively small second convex portion as described above, SpD is mainly adjusted by the volume average particle size and the mixing amount of the second resin particles.

[0060] First resin particles

[0061] The first resin particles having an elastic coefficient of 100 MPa or more and 10,000 MPa or less and high hardness generate a force for pushing out the colorant accumulated between the developing roller and the regulating member. If the elastic coefficient is less than 100 MPa, the hardness is insufficient, and the first resin particles are easily deformed by the pressure from the regulating member, so that the thrust is weakened. If the elastic coefficient is greater than 10,000 MPa, it is difficult to exert the effect of the present disclosure throughout the durability period due to increased damage to the colorant. The average elastic coefficient E1 described later is more preferably 100 MPa or more and 7,500 MPa or less, and E1 is further preferably 100 MPa or more and 2,000 MPa or less. The elastic coefficient of the first resin particles is adjusted to the above range by the molecular structure of the resin, the degree of crosslinking, etc.

[0062] Examples of the material of the first resin particles include polyurethane and acrylic resins. Among them, the resin particles may include polyurethane due to excellent strength.

[0063] Examples of the polyurethane contained in the first resin particles include ether-based polyurethane, ester-based polyurethane, acrylic-based polyurethane, polycarbonate-based polyurethane, and polyolefin-based polyurethane.

[0064] The volume average particle size of the first resin particles in the surface layer is preferably 10 μm or more and 20 μm or less. Since the first convex portion derived from the first resin particles easily protrudes outside the toner coating on the outer surface of the developing roller and effectively exerts a force to push out the toner, the volume average particle size can be set to 10 μm or more. A more preferred range is 13 μm or more and 18 μm or less. The volume average particle size is the volume average particle size of the first resin particles in a state contained in the surface layer formed by using the method described later, and the measurement method is also described later.

[0065] The content of the first resin particles in the surface layer is preferably 3% by volume or more and 25% by volume or less. When the content is set to 3% by volume or more, it is easy to make the first convex portion exist at a frequency sufficient to push out the toner. When the content is set to 25% by volume or less, since the toner between the developing roller and the regulating member is not easily disturbed at excessive frequencies, and the toner is not excessively damaged, it is also easy to exert the effect of the present disclosure throughout the second half of the durability period.

[0066] Second resin particles

[0067] The elastic coefficient of the second resin particles is 2 MPa or more and 50 MPa or less. If the elastic coefficient is less than 2 MPa, it is difficult to exert the effect of the present disclosure throughout the durability period, and if the elastic coefficient is greater than 50 MPa, the degree of sinking due to the pressure from the regulating member is low, so that the thrust of the first resin particles is not effectively transmitted to the toner. The elastic coefficient E2 of the second resin particles is adjusted to the above range by the molecular structure of the resin, the degree of crosslinking, etc.

[0068] Examples of the material of the second resin particles include polyurethane and silicones. Among them, the resin particles may include polyurethane due to excellent strength and flexibility.

[0069] The volume average particle size of the second resin particles in the surface layer is smaller than the volume average particle size of the first resin particles in the surface layer. As a result, the first convex portion derived from the first resin particles is made higher than the second convex portion derived from the second resin particles. The difference between the volume average particle size of the first resin particles and the volume average particle size of the second resin particles is preferably 5 μm or more and 15 μm or less. The difference can be set to 5 μm or more because the first resin particles protrude outside the toner coating and easily push out the toner, wherein the outer surface of the developing roller is coated with the toner. The difference can be set to 15 μm or less because a large amount of toner is prevented from entering between the developing roller and the regulating member. The volume average particle size of the second resin particles is preferably 3 μm or more and 10 μm or less. The volume average particle size can be set to 10 μm or less because it is easy to form a convex height difference sufficient for the first resin particles to push the toner. In addition, advantageously, the second convex portion derived from the second resin particles tends to be thinned at a high density, the toner easily follows the sinking second convex portion due to the pressure applied by the regulating member, and the thrust of the first resin particles is effectively exerted. The volume average particle diameter is more preferably 4 μm or more and 8 μm or less.The volume average particle diameter is the volume average particle diameter of the second resin particles in a state of being contained in a surface layer formed by using a method described later, and the measuring method is also described later.

[0070] The content of the second resin particles in the surface layer is preferably 15% by volume or more and 50% by volume or less. Since the second convex portions derived from the second resin particles tend to be thinned at a high density and sink due to the pressure applied by the regulating member, the content can be set to 15% by volume or more. When the content is set to 50% by volume or less, the portion of the second resin particles into which the toner is introduced is not excessive relative to the first resin particles from which the toner is pushed out, and the effect of the present disclosure is easily exerted.

[0071] Conductive agent

[0072] In order to control the conductivity of the surface layer, a conductive agent may be mixed in the surface layer. Examples of the conductive agent mixed in the surface layer include ionic conductive agents and electronic conductive agents such as carbon black. Among them, carbon black can be used because the conductivity of the surface layer and the toner charging performance of the surface layer are controllable. The volume resistivity of the surface layer is preferably within a range of 1.0×10 3 Ω·cm to 1.0×10 11 In the range of Ω·cm.

[0073] additive

[0074] The surface layer may contain various additives within the range that does not impair the characteristics of the present disclosure. For example, fine particles of inorganic compounds such as silicon dioxide mixed in the surface layer enable the surface layer to have reinforcing properties and can adjust the elastic coefficient Eb of the binder resin. In order to improve the performance required for the developing roller, such as improvement of the demoulding property of the toner and reduction of the dynamic friction coefficient, organic compound additives such as silicone oil may be mixed in the surface layer.

[0075] Method for forming surface layer

[0076] The method for forming the surface layer is not particularly limited, and the formation can be performed by using, for example, the following method. A coating liquid for forming a surface layer containing a binder resin, first resin particles, and second resin particles, and a conductive agent and additives according to appropriate needs is prepared. A substrate or a substrate provided with a conductive elastic layer is immersed in the coating liquid, and dried to form a surface layer on the substrate.

[0077] Next, the production method of the toner base particles according to the present disclosure will be described. The toner base particles can be produced by using a known method, and a kneading pulverization method or a wet production method can be used. From the viewpoint of uniform particle size and shape controllability, a wet production method can be used. Examples of wet production methods include suspension polymerization, dissolution suspension, emulsion polymerization aggregation, and emulsion aggregation, and the emulsion aggregation method can be used in the present disclosure.

[0078] The emulsion aggregation method is as follows. First, materials such as fine particles of a binder resin and a colorant are dispersed and mixed in an aqueous medium containing a dispersion stabilizer. A surfactant can be added to the aqueous medium. Subsequently, an aggregating agent is added to cause aggregation to have a predetermined colorant particle size. After or while the aggregation, the resin fine particles are melt-attached to each other. According to appropriate needs, shape control caused by heating is performed to form colorant particles. In this regard, the binder resin fine particles can be composite particles formed by multiple layers consisting of at least two resin layers with different compositions. For example, it can be produced by using an emulsion polymerization method, a mini-emulsion polymerization method, or a phase transition emulsification method, or it can be produced by combining some methods.

[0079] When the internal additive is contained in the toner base particles, the resin fine particles may contain the internal additive, or a dispersion of internal additive fine particles consisting only of the internal additive may be prepared separately, and the resulting internal additive fine particles may be aggregated simultaneously with the aggregation of the resin fine particles. Toner particles consisting of layers having different compositions may be formed by performing aggregation while adding resin particles having different compositions with a time difference during aggregation.

[0080] The following materials can be used as the dispersion stabilizer. Examples of the inorganic dispersion stabilizer include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silicon dioxide, and aluminum oxide.

[0081] Examples of the organic dispersion stabilizer include polyvinyl alcohol, gelatin, methyl cellulose, methyl hydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.

[0082] Known cationic surfactants, anionic surfactants and nonionic surfactants can be used as surfactants. Specific examples of cationic surfactants include dodecyl ammonium bromide, dodecyl trimethyl ammonium bromide, dodecyl pyridinium chloride, dodecyl pyridinium bromide and hexadecyl trimethyl ammonium bromide. Specific examples of nonionic surfactants include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, sorbitan monooleate polyoxyethylene ether, styryl phenyl polyoxyethylene ether and monodecanoyl sucrose. Specific examples of anionic surfactants include fatty soaps such as sodium stearate and sodium laurate, sodium lauryl sulfate, sodium dodecylbenzene sulfonate and polyoxyethylene (2) lauryl ether sodium sulfate.

[0083] The binder resin constituting the toner base particles will be described.

[0084] Vinyl resins, polyester resins, and the like can be examples of the binder resin. The following resins and polymers can be listed as examples of vinyl resins, polyester resins, and other binder resins.

[0085] Examples of binder resins include homopolymers of styrene or its substitution products such as polystyrene and polyvinyltoluene; styrene-based copolymers such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resins, polyamide resins, epoxy resins, polyacrylic resins, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or alicyclic hydrocarbon resins, and aromatic petroleum resins. These binder resins may be used alone or in combination.

[0086] The binder resin may contain a carboxyl group and is a resin produced by using a polymerizable monomer containing a carboxyl group. Examples include vinyl carboxylic acids such as acrylic acid, methacrylic acid, α-ethyl acrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives such as monoacryloxyethyl succinate, monomethacryloxyethyl succinate, monoacryloxyethyl phthalate, and monomethacryloxyethyl phthalate.

[0087] For polyester resin, materials produced by polycondensing the following carboxylic acid component and alcohol component can be used. Examples of carboxylic acid components include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. Examples of alcohol components include bisphenol A, hydrogenated bisphenol, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, glycerol, trimethylolpropane, and pentaerythritol.

[0088] The polyester resin may be a polyester resin containing a urea group. For the polyester resin, advantageously, the carboxyl group at the terminal or the like is not blocked.

[0089] In order to control the molecular weight of the binder resin constituting the toner base particles, a cross-linking agent may be added during the polymerization of the polymerizable monomer.

[0090] Examples of the cross-linking agent include ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, tetraethylene glycol diacrylate, diacrylates of each of polyethylene glycol #200, #400, and #600, dipropylene glycol diacrylate, polypropylene glycol diacrylate, and polyester diacrylate (produced by MANDA Nippon Kayaku Co., Ltd.) and methacrylates corresponding to the above-mentioned acrylates.

[0091] The amount of the cross-linking agent added is preferably 0.001% by mass or more and 15.000% by mass or less based on the polymerizable monomer.

[0092] In the present disclosure, a release agent may be contained as one of the materials constituting the toner base particles. In particular, when an ester wax having a melting point of 60° C. or more and 90° C. or less is used, a plasticizing effect is easily obtained due to excellent compatibility with a binder resin.

[0093] Examples of the ester wax used in the present disclosure include waxes mainly containing fatty acid esters such as carnauba wax and montanic acid ester wax; deacidified fatty acid esters from which some or all of the acid components are removed such as deacidified carnauba wax; methyl ester compounds obtained by, for example, hydrogenating vegetable oils and fats and having a hydroxyl group; saturated fatty acid monoesters such as stearyl stearate and behenyl behenate; diesters of saturated aliphatic dicarboxylic acids and saturated aliphatic alcohols such as disebendyl sebacate, distearyl dodecanedioate, and distearyl octadecanediol; and diesters of saturated aliphatic diols and saturated aliphatic monocarboxylic acids such as nonanediol disebendate and dodecanedioyl distearate.

[0094] These waxes may contain bifunctional ester waxes (diester) having two ester bonds in the molecular structure.

[0095] The difunctional ester wax is an ester compound of a diol and an aliphatic monocarboxylic acid or an ester compound of a dicarboxylic acid and an aliphatic monoalcohol.

[0096] Specific examples of the aliphatic monocarboxylic acids include myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, oleic acid, vaccenic acid, linoleic acid, and linolenic acid.

[0097] Specific examples of the aliphatic monohydric alcohol include myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, and triacontanol.

[0098] Specific examples of dicarboxylic acids include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0099] Specific examples of the diols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosandiol, 1,30-triacontandiol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiroglycol, 1,4-phenylene glycol, bisphenol A, and hydrogenated bisphenol A.

[0100] Examples of other usable release agents include petroleum waxes such as paraffin wax, microcrystalline wax, and vaseline and their derivatives, montan wax and its derivatives, hydrocarbon waxes and their derivatives obtained by using the Fischer-Tropsch process, polyolefin waxes such as polyethylene and polypropylene and their derivatives, natural waxes such as carnauba wax and candelilla wax and their derivatives, higher fatty alcohols, and fatty acids such as stearic acid and palmitic acid and their compounds. The content of the release agent is preferably 5.0 parts by mass or more and 20.0 parts by mass or less relative to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0101] In the present disclosure, there is no particular limitation on the colorant contained in the toner particles, and the following known materials can be used.

[0102] For yellow pigments, yellow iron oxide, Naples yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and condensed azo compounds such as lemon yellow lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds are used. Specific materials are as follows.

[0103] Specific materials include CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, and 180.

[0104] Examples of red pigments include red iron oxide, permanent red 4R, lithotripter red, pyrazolone red, apparent red calcium salt, lake red C, lake red D, brilliant magenta 6B, brilliant magenta 3B, eosin lake, rhodamine lake B, condensed azo compounds such as alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific materials are described below.

[0105] Specific materials include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254.

[0106] Examples of blue pigments include basic blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, copper phthalocyanine compounds such as Indanthrene Blue BG and derivatives thereof, anthraquinone compounds, and basic dye lake compounds. Specific materials are as follows.

[0107] Specific materials include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.

[0108] Examples of black pigments include carbon black and aniline black. These colorants may be used alone, in combination, or in the state of a solid solution.

[0109] The content of the colorant is preferably 3.0 parts by mass or more and 15.0 parts by mass or less relative to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0110] In the present disclosure, the toner base particles may contain a charge control agent. For the charge control agent, known materials may be used. In particular, a charge control agent having a high charging speed and capable of stably maintaining a constant charge amount may be used.

[0111] The material used as the charge control agent and providing negative chargeability to the toner particles is as follows.

[0112] Examples of materials include organometallic compounds and chelate compounds such as monoazo metal compounds, acetylacetonate metal compounds, aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, and metal compounds of hydroxycarboxylic acids and dicarboxylic acids. Other examples of materials include aromatic hydroxycarboxylic acids, aromatic monocarboxylic acids, and aromatic polycarboxylic acids and their metal salts, anhydrides, and esters, and phenol derivatives such as bisphenol. In addition, urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarene are included.

[0113] Meanwhile, examples of charge control agents that provide the toner particles with a positively charged property include aniline black and aniline black modified with fatty acid metal salts and the like; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzyl-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate; onium salts such as phosphonium salts as analogs of these and lake pigments of these; triphenylmethane dyes and lake pigments of these (the color formers are phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferrocyanide, and ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents.

[0114] The charge control agent may be contained alone, or at least two kinds may be contained in combination. The amount of the charge control agent added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less relative to 100.00 parts by mass of the polymerizable monomer.

[0115] Next, the external additive A used in the present disclosure will be described.

[0116] There is no particular limitation on the production method of the external additive A used in the present disclosure, and a sol-gel method may be employed. A method of producing silica particles by using a sol-gel method will be described below.

[0117] First, in an organic solvent in the presence of water, alkoxysilane is subjected to hydrolysis and condensation reaction by using a catalyst to obtain a silica sol suspension. Subsequently, the solvent is removed from the silica sol suspension and dried to obtain silica fine particles.

[0118] The major diameter of the silica particles produced by the sol-gel method is controllable by the reaction temperature, the dropping speed of the alkoxysilane, the weight ratio of water to the organic solvent and the catalyst, and the stirring speed during the hydrolysis and condensation reaction steps.

[0119] Generally, the silica particles thus obtained have hydrophilicity and many surface silanol groups. As a result, when the silica particles are used as an external additive for toner, the surface of the silica particles can be subjected to a hydrophobic treatment.

[0120] Examples of the hydrophobic treatment method include a method in which the solvent is removed from the silica sol suspension, dried, and treated with a hydrophobic treatment agent, and a method in which the hydrophobic treatment agent is directly added to the silica sol suspension and treated while drying. From the viewpoint of controlling the half value width of the particle size distribution and controlling the saturated water adsorption amount, a method in which the hydrophobic treatment agent is directly added to the silica sol suspension can be adopted.

[0121] Examples of the hydrophobization method include a method in which a chemical treatment with an organosilicon compound that reacts with or physically adsorbs silica is performed. In a favorable method, silica produced by vapor phase oxidation of a silicon halogen compound is treated with an organosilicon compound.

[0122] Such organosilicon compounds are described below.

[0123] Examples of the organic silicon compound include hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, methyltrichlorosilane, allyldimethylchlorosilane, allylphenyldichlorosilane, and benzyldimethylchlorosilane.

[0124] Examples of the organosilicon compound further include bromomethyldimethylchlorosilane, α-chloroethyltrichlorosilane, β-chloroethyltrichlorosilane, chloromethyldimethylchlorosilane, triorganosilylmercaptan, trimethylsilylmercaptan, and triorganosilyl acrylate.

[0125] Examples further include vinyldimethylacetoxysilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, and 1-hexamethyldisiloxane.

[0126] Examples further include 1,3-divinyltetramethyldisiloxane, 1,3-diphenyltetramethyldisiloxane, and dimethylpolysiloxane having 2 to 12 siloxane units per molecule and having one hydroxyl group bonded to each Si in the unit located at the terminal.

[0127] These may be used alone, or at least two kinds may be used in combination.

[0128] For silicone oil treated silica, the viscosity at 25°C is preferably 30 mm 2 / s or more and 1,000mm 2 / s or less silicone oil.

[0129] Examples of the silicone oil include dimethyl silicone oil, methylphenyl silicone oil, α-methylstyrene-modified silicone oil, chlorophenyl silicone oil, and fluorine-modified silicone oil.

[0130] The method of silicone oil treatment is as follows.

[0131] Examples of the method include a method in which silica treated with a silane coupling agent and silicone oil are directly mixed by using a mixer such as an FM mixer, a method in which silicone oil is sprayed onto silica as a base, and a method in which silicone oil is dissolved or dispersed in an appropriate solvent, silica is added and mixed, and the solvent is removed.

[0132] For silicone oil-treated silica, the silica after silicone oil treatment may be heated to a temperature of 200° C. or higher (more preferably 250° C. or higher) in an inert gas to stabilize the surface coating.

[0133] In addition, in order to promote monodispersion of silica fine particles on the toner particle surfaces, or to exert a stable spacer effect, silica particles may be produced by a pulverization treatment.

[0134] The major diameter of the external additive B used in the present disclosure is 5 nm or more and less than 40 nm. The external additive B may be wet silica produced by a precipitation method, a sol-gel method, or the like, or dry silica produced by a vaporized metal combustion method, a gas phase method, or the like, and may be dry silica.

[0135] The raw material for forming dry silica may be a silicon halogen compound or the like.

[0136] Silicon tetrachloride is used as the silicon halogen compound. Silane such as methyltrichlorosilane and trichlorosilane may be used alone as a raw material, or silicon tetrachloride and silane in a mixture state may be used as a raw material.

[0137] The predetermined silicon dioxide can be obtained by a so-called flame hydrolysis reaction in which a raw material is gasified and reacted with water generated as an intermediate material in a hydrogen-oxygen flame.

[0138] For example, thermal decomposition and oxidation reaction of silicon tetrachloride gas in oxygen and hydrogen is utilized, and the reaction formula is as follows.

[0139] SiCl4+2H2+O2→SiO2+4HCl

[0140] A method for producing dry silica will be described below.

[0141] Oxygen is supplied to the burner, and the ignition burner is ignited. Thereafter, hydrogen is supplied to the burner to form a flame, silicon tetrachloride used as a raw material is introduced into the flame to be gasified. Subsequently, at least a flame hydrolysis reaction is caused to occur, and the resulting silicon dioxide powder is recovered.

[0142] The average diameter is adjustable by appropriately changing the flow rate of silicon tetrachloride, the flow rate of supplied oxygen, the flow rate of supplied hydrogen, and the residence time of silicon dioxide in the flame.

[0143] The external additive B may also be subjected to a surface treatment similar to the surface treatment of the external additive A.

[0144] The measurement method of each physical property according to the present disclosure will be described below.

[0145] The average value of the maximum height Rz of the developing roller

[0146] The average value of the maximum height Rz according to the present disclosure can be measured by scanning the outer surface of the surface layer of the developing roller with a laser microscope (trade name: VK-X150, produced by KEYENCE CORPORATION).

[0147] First, the developing roller is set so that the vertex in the circumferential direction of the outer surface of the developing roller is directly below the lens of the laser microscope, and the axial direction of the developing roller is consistent with the length direction in the field of view observed by the laser microscope. Subsequently, the shape of the outer surface of the surface layer is measured under the following conditions.

[0148] Mode: Shape Measurement Expert

[0149] Measuring lens: Magnification 50 times

[0150] Z-axis upper and lower limits: Points where reflected light is no longer observable in the laser field of view

[0151] Laser brightness: automatic

[0152] Dual scan: Always

[0153] Measuring Mode: Surface Shape

[0154] Measurement size: High definition (2048×1536)

[0155] Measurement quality: high precision

[0156] RPD: On

[0157] Pitch: 0.13μm

[0158] Next, the above measurement results are read by a multi-file analysis application which is software attached to the laser microscope. The read image is corrected as follows.

[0159] Surface shape correction:

[0160] Correction method: quadratic surface correction, specification method: area specification

[0161] Height Cut Level:

[0162] Reduction level: Strong

[0163] smooth:

[0164] Size: 7×7, Type: Single Average

[0165] Next, the average value of Rz was calculated under the following conditions.

[0166] Measuring mode: "Multi-line roughness"

[0167] Measuring area: Horizontal line

[0168] Peripheral lines: 18

[0169] Interval: Skip 20 lines

[0170] Measured value: Average value of Rz

[0171] The above measurement was performed at 5 equally spaced locations in the axial direction of the developing roller × 6 equally spaced locations in the circumferential direction, a total of 30 locations, and the arithmetic mean thereof was taken as the average value of the maximum height Rz of the developing roller Z-1. As a result, the average value of the maximum height Rz according to the present embodiment was the average value of the maximum height Rz at a total of 540 points of 18 lines × 30 points in a short distance, and therefore, indicated the height and frequency of the higher convex portions on the outer surface of the surface layer.

[0172] Peak vertex density SpD

[0173] The peak vertex density SpD is obtained by surface observation under a microscope in the same manner as the average value of the maximum heights Rz. First, the shape of the outer surface of the developing roller is measured in the same manner as the average value of the maximum heights Rz described above.

[0174] Subsequently, the above measurement results are read by a multi-file analysis application as software attached to the laser microscope. The read image is corrected in the same manner as the average value of the maximum height Rz.

[0175] Next, SpD was calculated under the following conditions.

[0176] Measuring mode: "Surface roughness"

[0177] Measuring area: The entire area

[0178] Measured value: SpD

[0179] The above measurement was performed at 5 locations with equal spacing in the axial direction of the developing roller and 6 locations with equal spacing in the circumferential direction, a total of 30 locations, and the value was calculated every mm. 2 The arithmetic mean of the peak apex density SpD of the developing roller is taken as the peak apex density SpD of the developing roller.

[0180] Confirmation of the first convex portion and the second convex portion

[0181] The height difference between the first convex portion and the second convex portion on the outer surface of the surface layer of the developing roller is determined by surface observation under a microscope in the same manner as the average value of the above-mentioned maximum height Rz. First, the shape of the outer surface of the developing roller is measured in the same manner as the average value of the above-mentioned maximum height Rz.

[0182] Subsequently, the above measurement results are read by a multi-file analysis application as software attached to the laser microscope. The read image is corrected in the same manner as the average value of the maximum height Rz.

[0183] Next, in measurement mode: "multi-line roughness", the apex of a relatively large convex portion present in the observation field is connected to the apex of a relatively small convex portion by specifying two points, and two convex portions where the height difference between the apex of the large convex portion and the apex of the small convex portion is 5.0 μm or more are extracted.

[0184] The outer surface of the developer roller is marked so that the large convex portion and the small convex portion are distinguished from each other. Subsequently, the developer roller is cooled to -150°C, and the rubber slice is cut by using a cryo-microtome (UC-6 (product name), produced by Leica Microsystems) so that the cross section of the surface layer in the thickness direction shows the apex of the convex portion including the two marks.

[0185] Measurement of elastic coefficients of first resin particles and second resin particles

[0186] A scanning probe microscope (SPM) (trade name: MFP-3D-Origin, produced by Oxford Instruments) was used for measurement. Specifically, the rubber slice produced as described above was placed under a room temperature of 23°C and a humidity of 50% for 24 hours. Thereafter, the resulting rubber slice was placed on a silicon wafer, and the silicon wafer was set on the stage of the scanning probe microscope. The cross-sectional portion of the surface layer of the rubber slice was scanned by a probe (AC160 (product name), produced by Olympus Corporation). In this regard, the conditions of the probe were set to a spring constant of 28.23nN / nm, a pulse constant of 82.59nm / V, and a resonance frequency of 282kHz (first order) and 1.59MHz (higher order). For other measurement conditions, the measurement mode of the SPM was set to an AM-FM probe, the free amplitude of the probe was set to 3V, and the amplitude of the set point was set to 2V (first order) and 25mV (higher order). In a field size of 20 μm×20 μm, the scanning speed was set to 1 Hz, and the number of scanning points was set to 256 points vertically and 256 points horizontally.

[0187] Thereafter, 10 measurement points are specified near the center of the resin particles of the rubber slice in the thickness direction of the surface layer, and the force curve is obtained at each measurement point in the contact mode. In this respect, the conditions for obtaining the force curve are as follows. The force curve is obtained under the conditions that the trigger value is 0.2 to 0.5V (changed according to the hardness), the distance of measuring the force curve is 500nm, and the scanning speed is 1Hz (the speed of making the probe go back and forth once). Thereafter, each force curve is fitted according to the Hertz theory. From the obtained results, the highest and lowest values ​​are removed, and the arithmetic mean of eight points is determined, and it is taken as the elastic coefficient of each measurement area. The particles with an elastic coefficient of more than 100MPa and less than 10,000MPa are represented as the first resin particles, and the particles with an elastic coefficient of more than 2MPa and less than 50MPa are represented as the second resin particles.

[0188] For each of the first resin particles and the second resin particles, the above measurement is performed for a total of 45 or more particles at a total of 9 or more points of 3 or more equally spaced points in the axial direction of the developing roller × 3 or more equally spaced points in the circumferential direction. Subsequently, the arithmetic mean of the first resin particles is taken as the average elastic coefficient E1 of the first resin particles, and the arithmetic mean of the second resin particles is taken as the average elastic coefficient E2 of the second resin particles.

[0189] Elastic modulus of surface matrix

[0190] The elastic coefficient Eb of the surface layer substrate is measured as described below.

[0191] The elastic modulus of the surface layer matrix in the region of 1.1 to 1.2 μm in the depth direction from the outer surface of the surface layer in the cross section in the thickness direction of the surface layer is measured by using the above-mentioned method.

[0192] Next, the elastic coefficient was similarly measured in an area with a pitch of 1.0 μm in the depth direction from the above area to the vicinity of the interface of the above conductive elastic layer. In this regard, the measurement in the contact mode was performed while avoiding the conductive agent, filler, etc. The above measurement was performed at a total of 9 or more points of 3 or more equally spaced points in the axial direction of the developing roller × 3 or more equally spaced points in the circumferential direction, and the arithmetic mean value thereof was taken as the elastic coefficient Eb of the surface layer matrix.

[0193] Volume average particle size D1 and D2 of resin particles and volume ratio

[0194] The volume average particle diameters D1 and D2 of the resin particles present in the surface layer are measured by using the following method.

[0195] All resin particles present in the surface layer cross section for measurement of the elastic coefficient are classified into first resin particles and second resin particles based on the measurement result of the elastic coefficient, and the circle equivalent diameter Ds of the cross section of each particle is calculated from the cross-sectional area of ​​each particle. Assuming that each particle is a sphere and the cross section is a cross section obtained by randomly cutting the sphere, the particle size D of the resin particle is calculated from the circle equivalent diameter Ds of the cross section based on the following formula (1).

[0196] therefore

[0197] D=4 / π×D s (1)

[0198] The above measurement is performed for 100 or more particles of each of the first resin particles and the second resin particles at a total of 9 or more points (3 or more equally spaced points in the axial direction of the developing roller × 3 or more equally spaced points in the circumferential direction). The D of each particle thus obtained and the D / 2 obtained by using 4 / 3×π×(D / 2) are used. 3 The obtained volume values ​​are converted to calculate volume average particle diameters (median diameters) D1 and D2 of the first resin particles and the second resin particles, respectively.

[0199] As can be understood from Tables 3, 5, and 6, there is a favorable correlation between the volume average particle size of the surface layer and the volume average particle size (also simply referred to as average particle size) of particles used as a raw material.

[0200] In addition, the volume ratio of the first resin particles and the second resin particles in the surface layer is equal to the area ratio obtained from the cross-sectional area, and therefore, is calculated by using the cross-section measured above. Specifically, all resin particles present in the cross section of the surface layer are classified into the first resin particles and the second resin particles based on the elastic coefficient, and the area ratio of the first resin particles and the second resin particles relative to the cross-sectional area of ​​the surface layer is calculated. The measurement is performed at a total of 9 or more points of 3 or more equally spaced points in the axial direction of the developing roller × 3 or more equally spaced points in the circumferential direction, and the arithmetic mean thereof is taken as the volume ratios V1 and V2 of the first resin particles and the second resin particles, respectively.

[0201] Measurement of the major diameters of external additives A and B

[0202] The surface of the toner particles was photographed at a magnification of 50,000 times by using FE-SEMS-4800 (produced by Hitachi, Ltd.). The long diameter of the external additive was measured by using the magnified image, and the additive having a long diameter of 40 nm or more and 400 nm or less was represented as the external additive A. The additive having a long diameter of 5 nm or more and less than 40 nm was represented as the external additive B. The measurement was performed for 100 particles of each of the external additive A and the external additive B, and the average value of the long diameter of the external additive A was represented as the average long diameter Da, and the average value of the long diameter of the external additive B was represented as the average long diameter Db.

[0203] This also applies to toners containing multiple external additives on the surface of toner particles. When the reflected electron image is observed with S-4800, the elements of each fine particle can be identified by using elemental analysis such as EDAX. In addition, the same fine particles can be selected based on features such as shape. The above measurement of the same fine particles enables the major diameter to be calculated based on the type of fine particles.

[0204] Dispersion evaluation index of external additive A on toner surface

[0205] The calculation was performed from the observed image for measuring the major diameters of the external additive A and the external additive B by using the image processing software "ImageJ".

[0206] Only external additive particles with a major diameter of 40 nm or more and 400 nm or less are selected on the software, binarized, the number of external additive particles n and the centroid coordinates of all external additive particles are calculated, and the distance dnmin between each external additive and the nearest external additive particle is calculated. When the average value of the nearest distance is expressed as dave, the dispersion evaluation index is expressed by the following formula (2).

[0207]

[0208] Randomly selected 50 toner particles are observed, the dispersion evaluation index is determined, and the average value thereof is expressed as the dispersion evaluation index.

[0209] Coverage of external additive A and external additive B

[0210] The coverage of the external additive A and the external additive B according to the present disclosure is measured based on an observed image for determining the major diameters of the external additive A and the external additive B. Calculation based on the observed image is performed by using the image processing software "ImageJ" as described below.

[0211] Only particles originating from external additive A with a long diameter of 40 nm or more and 400 nm or less in the image are selected on the software. Subsequently, the selected area of ​​the screen is displayed by setting the measurement. The resulting value is divided by the area of ​​the entire field of view and taken as the coverage of external additive A in the field of view of interest. This measurement is performed for 100 fields of view, and the average value thereof is expressed as the coverage of external additive A. In addition to selecting particles originating from external additive B with a long diameter of 5 nm or more and less than 40 nm in the image on the software, the coverage of external additive B is determined in the same manner as the coverage of external additive A.

[0212] Method for measuring the total fixation rate of external additive A and external additive B

[0213] A concentrated sucrose liquid was prepared by adding 160 g of sucrose (produced by KISHIDA CHEMICAL Co., Ltd.) to 100 mL of deionized water and heating the resulting liquid in hot water for dissolution. A dispersion was produced by placing 31 g of the concentrated sucrose liquid and 6 mL of Contaminon N (a 10% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments composed of a nonionic surfactant, an anionic surfactant, and an organic auxiliary agent at pH 7, produced by Wako Pure Chemical Industries, Ltd.) in a centrifugal separation tube (capacity 50 mL). The resulting dispersion was mixed with 1.0 g of a toner, and the aggregates of the toner were disentangled by using a scraper or the like.

[0214] The centrifuge tube was vibrated at 350 spm (strokes per min) for 20 minutes by using a vibrator. After vibration, the solution was transferred to a swing rotor glass tube (capacity of 50 mL) and separated by using a centrifuge (H-9R produced by KOKUSAN Co., Ltd.) at 3,500 rpm and 30 minutes. Visual inspection showed that the toner was fully separated from the solution, and the toner separated as the uppermost layer was removed with a scraper or the like. The removed aqueous solution containing the toner was filtered by using a vacuum filter. Thereafter, drying was performed by using a dryer for more than 1 hour. The dried product was crushed with a scraper, and the amount of silicon was measured by X-ray fluorescence. The fixation rate (%) was calculated from the ratio of the measured amount of the toner after washing to the target element in the toner in the initial stage.

[0215] X-ray fluorescence measurement of each element was performed in compliance with IS K 0119-1969 and is specifically described below.

[0216] For the measuring equipment, a wavelength dispersive X-ray fluorescence spectrometer "Axios" (produced by PANalytical) and accompanying dedicated software "SuperQ version 4.OF" (produced by PANalytical) for setting measurement conditions and analyzing measurement data were used. In this respect, Rh was used as the anode of the X-ray tube, the measurement atmosphere was set to vacuum, the measurement diameter (collimator mask diameter) was set to 10 mm, and the measurement time was set to 10 seconds. When measuring light elements, detection was performed by using a proportional counter (PC), and when measuring heavy elements, detection was performed by using a scintillation counter (SC).

[0217] For the measurement sample, about 1 g of the washed toner or the toner in the initial stage was placed in a special pressed aluminum ring with a diameter of 10 mm and flattened. Pellets with a thickness of about 2 mm were used, which were press-formed at 20 MPa for 60 seconds using a table tablet press "BRE-32" (produced by MAEKAWA TESTING MACHINE MFG. Co., Ltd.).

[0218] The measurement was performed under the above conditions, the element was identified based on the position of the obtained X-ray peak, and the concentration of the element was calculated from the count rate (unit: cps) which is the number of X-ray photons per unit time.

[0219] A quantitative method for, for example, silicon in the toner will be described. For example, 0.5 parts by mass of silicon dioxide (SiO2) fine powder is added to 100 parts by mass of toner particles, and mixed thoroughly by using a coffee grinder. Likewise, 2.0 parts by mass or 5.0 parts by mass of silicon fine powder is mixed with toner particles, and these are used as samples for forming a calibration curve.

[0220] For each sample, the sample pellets for forming the calibration curve were produced by using a table tablet press as described above, and the count rate (unit: cps) of Si-Kα rays observed at a diffraction angle (2θ) of 109.08° was measured, wherein PET was used as a scattering crystal. At this time, the acceleration voltage and current value of the X-ray generator were set to 24 kV and 100 mA, respectively. The obtained calibration curve is a linear function, the vertical axis represents the obtained X-ray count rate, and the horizontal axis represents the amount of SiO2 added to each sample for forming the calibration curve.

[0221] The target toner was pelletized by using a tablet press as described above, and its Si-Kα ray count rate was measured. Subsequently, the content of the organic silicon polymer in the toner was determined based on the calibration curve. The ratio of the amount of the element in the toner after washing to the amount of the element in the toner in the initial stage was determined, the amount was calculated by using the above method, and taken as the fixing rate (%).

[0222] Measurement of toner particle size

[0223] A precision particle size distribution analyzer based on the pore impedance method (trade name: Coulter CounterMultisizer 3) and dedicated software (trade name: Beckman Coulter Multisizer 3Version 3.51, produced by Beckman Coulter, Inc.) were used. The aperture used was 100 μm, and the measurement was performed with 25,000 effective measurement channels, the measurement data was analyzed, and the calculation was performed. For the aqueous electrolyte solution used for measurement, a solution in which analytical grade sodium chloride was dissolved in deionized water so that the concentration was about 1% by mass was used, for example, ISOTONII (trade name) produced by Beckman Coulter, Inc. Before performing measurement and analysis, the dedicated software was set as described below.

[0224] In the "Change Standard Measurement Method (SOM)" screen of the dedicated software, the total count in the control mode was set to 50,000 particles, the number of measurements was set to 1, and the Kd value was set to a value obtained by using "Standard Particles 10.0 μm" (produced by Beckman Coulter, Inc.). The threshold value and noise level were automatically set by pressing the "Threshold / Noise Level Measurement Button". In addition, the current was set to 1,600 μA, the gain was set to 2, the electrolyte solution was set to ISOTON II (trade name), and "Rinse the orifice tube after measurement" was checked.

[0225] In the "Set Pulse to Size Conversion" screen of the dedicated software, set the element spacing to logarithmic size, the size elements to 256 size elements, and the size range to 2 μm or more and 60 μm or less.

[0226] The specific measurement method is described as follows.

[0227] (1) Fill a 250-mL glass round-bottom beaker dedicated to Multisizer 3 with about 200 mL of electrolyte aqueous solution, place the beaker on the sample stand, and stir counterclockwise at 24 rpm with a stirring rod. Then, remove dirt and bubbles in the nozzle by the "swimming nozzle flushing" function of the analysis software.

[0228] (2) A 100 mL flat-bottomed glass beaker was filled with about 30 mL of an aqueous electrolyte solution. About 0.3 mL of a dilution prepared by diluting 3 times by mass "CONTAMINON N" (trade name) (a 10% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments, produced by Wako Pure Chemical Industries, Ltd.) with deionized water was added to the beaker.

[0229] (3) A predetermined amount of deionized water and 2 mL of CONTAMINON N (trade name) were added to a water tank of an ultrasonic dispersing device (Ultrasonic Dispersion System Tetora 150 manufactured by NikkakiBios Co., Ltd.) having an oscillation frequency of 50 kHz, two oscillators shifted 180° from each other and an electrical output of 120 W.

[0230] (4) The beaker according to (2) above is set in the beaker fixing hole of the ultrasonic dispersing device, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker becomes the maximum level.

[0231] (5) In a state where the electrolyte aqueous solution in the beaker according to (4) above is irradiated with ultrasonic waves, about 10 mg of the toner (particles) is gradually added to the electrolyte aqueous solution and dispersed. Subsequently, the ultrasonic dispersion treatment is further continued for 60 seconds. In this regard, during the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to become 10° C. or more and 40° C. or less.

[0232] (6) The electrolyte aqueous solution containing the dispersed toner (particles) according to (5) above is dropped into the round-bottomed beaker set in the sample stage according to (1) above by using a pipette to adjust the measurement concentration to about 5%. Subsequently, measurement is performed until the number of particles measured reaches 50,000.

[0233] (7) The weight average particle diameter (D4) is calculated by analyzing the measurement data with the dedicated software connected to the device. In this regard, when the dedicated software is set to the graph / volume % setting, the "average diameter" on the "analysis / volume statistics (arithmetic mean)" screen is equivalent to the weight average particle diameter (D4). When the dedicated software is set to the graph / number %, the "average diameter" on the "analysis / number statistics (arithmetic mean)" screen is equivalent to the number average particle diameter (D1).

[0234] Example

[0235] The present disclosure will be specifically described below based on Examples and Comparative Examples. However, the present disclosure is not limited to these Examples, etc. Unless otherwise specified, all "parts" and "%" used in Examples and Comparative Examples are based on mass.

[0236] Example 1

[0237] Production Example of Toner Particles

[0238] Production Example of Toner Particles 1

[0239] A production example of the toner particles 1 will be described.

[0240] Preparation of Binder Resin-Particle Dispersion

[0241] The solution is produced by mixing 89.5 parts of styrene, 9.2 parts of butyl acrylate, 1.3 parts of acrylic acid, and 3.2 parts of n-lauryl mercaptan. An aqueous solution consisting of 1.5 parts of NEOGEN RK (produced by Dai-ichi Kogyo Seiyaku Co., Ltd.) and 150 parts of deionized water is added to the resulting solution and dispersed. While further slowly stirring for 10 minutes, an aqueous solution consisting of 0.3 parts of potassium persulfate and 10 parts of deionized water is added. After replacement with nitrogen, emulsion polymerization is carried out at 70°C for 6 hours. After the polymerization is completed, the reaction solution is cooled to room temperature, and deionized water is added to obtain a resin-particle dispersion having a solid content concentration of 12.5% ​​by mass and a median diameter of 0.2 μm based on volume.

[0242] Preparation of release agent dispersion

[0243] A release agent dispersion was obtained by mixing 100 parts of a release agent (behenyl behenate, melting point: 72.1° C.) and 15 parts of NEOGEN RK in 385 parts of deionized water and dispersing for 1 hour using a wet jet mill JN100 (produced by JOKOH CO., LTD.) The concentration of the release agent dispersion was 20% by mass.

[0244] Preparation of colorant dispersion

[0245] A colorant dispersion liquid was obtained by mixing 100 parts of carbon black "Nipex 35 (produced by Orion Engineered Carbons)" used as a colorant and 15 parts of NEOGEN RK in 885 parts of deionized water, and performing dispersion for 1 hour by using a wet jet mill JN100.

[0246] Preparation of toner particles 1

[0247] A homogenizer (ULTRA-TURRAX T50 manufactured by IKA) was used to disperse 265 parts of a resin-particle dispersion, 10 parts of a wax dispersion, and 10 parts of a colorant dispersion. The temperature in the container was adjusted to 30°C while stirring, and 1 mol / L hydrochloric acid was added to adjust the pH to 5.0. Associated particles were generated by starting the temperature rise after standing for 3 minutes and by raising the temperature to 50°C. In this state, the particle size of the associated particles was measured by using a Coulter Counter Multisizer 3 (registered trademark, manufactured by Beckman Coulter, Inc.). When the weight-average particle size reached 6.8 μm, 1 mol / L sodium hydroxide aqueous solution was added to adjust the pH to 8.0 to stop the particle growth.

[0248] Thereafter, the temperature was raised to 95° C. to perform melt adhesion and spheroidization of the united particles. When the average circularity reached 0.980, the temperature was started to be lowered, and the temperature was lowered to 30° C. to obtain a toner-particle dispersion liquid 1.

[0249] Hydrochloric acid was added to the obtained toner-particle dispersion 1 to adjust the pH to 1.5, stirred for 1 hour, and after standing, solid-liquid separation was performed by using a pressure filter to obtain a toner cake. The obtained cake was re-pulped by using deionized water to form a dispersion again. Thereafter, solid-liquid separation was performed by using the above-mentioned pressure filter. The re-pulping operation and solid-liquid separation were repeated until the conductivity of the filtrate became 5.0 μS / cm or less, and the final solid-liquid separation was performed to obtain a toner cake. The obtained toner cake was dried by using a flash jet dryer Flash Jet Dryer (produced by SEISHINENTERPRISE CO., LTD.). For the drying conditions, the blowing temperature was 90°C, the dryer outlet temperature was 40°C, and the cake supply speed was adjusted to a speed at which the outlet temperature did not deviate from 40°C according to the water content of the toner cake. In addition, fine powder and coarse powder were cut by using a multi-division classifier utilizing the wall effect to obtain a toner base particle 1.

[0250] Production Example of Silica Granules 1

[0251] 589.6g of methanol, 42.0g of water, and 47.1g of 28% by mass ammonia water were added to a 3L glass reactor equipped with a stirrer, a dropping funnel, and a thermometer, and mixed. The temperature of the resulting solution was adjusted to 35°C, and 1,100.0g (7.23mol) of tetramethoxysilane and 395.2g of 5.4% by mass ammonia water were added simultaneously while stirring. Tetramethoxysilane was added dropwise within 6 hours, and ammonia water was added dropwise within 5 hours. After the addition was completed, stirring was further continued for 0.5 hours to hydrolyze. As a result, a methanol-water dispersion of hydrophilic spherical sol-gel silica fine particles was obtained. Subsequently, an ester adapter and a cooling tube were connected to the glass reactor, and the above dispersion was fully dried under reduced pressure at 80°C. The above steps were performed several dozen times, and the resulting silica particles were pulverized by using a pulverizer (produced by Hosokawa Micron Corporation).

[0252] Thereafter, 500 g of silica particles were placed in a polytetrafluoroethylene inner cylinder type stainless steel autoclave with an internal volume of 1,000 ml. After replacing the interior of the autoclave with nitrogen, while the stirring blade connected to the autoclave was rotated at 400 rpm, 0.5 g of hexamethylenedisilazane (HMDS) and 0.1 g of water were atomized by using a two-fluid nozzle to evenly blow to the silica powder. After stirring for 30 minutes, the autoclave was sealed and heated at 200° C. for 2 hours. Subsequently, ammonia was removed by decompressing the interior of the system while heating to obtain silica particles 1.

[0253] Production Example of Silica Granules 9

[0254] 100 parts of dry silica fine powder (BET specific surface area: 300 m 2 / g) is subjected to a hydrophobic treatment.

[0255] Production Example of Toner 1

[0256] In the mixing step 1, the toner particles 1 and the silica particles 1 are mixed by using an FM mixer (Model FM10C, manufactured by NIPPON COKE & ENGINEERING CO., LTD.).

[0257] In a state where the water temperature in the jacket of the FM mixer was stabilized at 25°C±1°C, 100 parts of toner particles 1 and 0.75 parts of silica particles 1 were put into the mixer. Mixing was started at a rotating blade speed of 400 rpm, and mixing was performed for 2 minutes while the water temperature and flow rate in the jacket were controlled so that the temperature in the tank was stabilized at 25°C±1°C, thereby obtaining a mixture of toner particles 1 and silica particles 1.

[0258] In the mixing step 2, an FM mixer (Model FM10C, manufactured by NIPPON COKE & ENGINEERING CO., LTD.) was used, and silica particles 9 were added to the mixture of toner particles 1 and silica particles 1. In a state where the water temperature in the jacket of the FM mixer was stabilized at 40°C±1°C, 1.5 parts of silica particles 9 were put into the mixer relative to 100 parts of toner particles 1. Mixing was started at a rotating blade rotation speed of 3,600 rpm, and mixing was performed for 10 minutes while the water temperature and flow rate in the jacket were controlled so that the temperature in the tank was stabilized at 40°C±1°C, thereby obtaining a mixture of toner particles 1, silica particles 1, and silica particles 9.

[0259] Further, in the mixing step 3, an FM mixer (Model FM10C manufactured by NIPPON COKE & ENGINEERING CO., LTD.) was used, and silica particles 1 were added to the mixture of toner particles 1, silica particles 1, and silica particles 9 obtained in the mixing step 2. In a state where the water temperature in the jacket in the FM mixer was stabilized at 25°C±1°C, 0.75 parts of silica particles 1 relative to 100 parts of toner particles 1 were put into the mixer. Mixing was started at a rotating blade rotation speed of 2,000 rpm, and mixing was performed for 10 minutes while the water temperature and flow rate in the jacket were controlled so that the temperature in the tank was stabilized at 25°C±1°C, and toner 1 was obtained by screening through a mesh having a mesh opening of 75 μm. Table 1 describes the production conditions of toner 1, and Table 2 describes the physical properties.

[0260] Table 1

[0261]

[0262] Table 2

[0263]

[0264] Production Example of Developing Roller 1

[0265] Production of conductive elastic layer roller

[0266] Production of Conductive Elastic Layer Roller 1

[0267] As a substrate, a SUS304 mandrel having an outer diameter of 6 mm and a length of 260 mm coated with a primer (trade name: DY35-051, produced by Dow Corning Toray Co., Ltd.) was prepared and baked. The resulting substrate was put into a mold, and an addition type silicone rubber composition in which the materials described in Table 3 were mixed was injected into a cavity formed in the mold. Subsequently, the mold was heated so that the addition type silicone rubber composition was cured by heating at a temperature of 150° C. for 15 minutes, and demolded. Thereafter, the curing reaction was completed by further heating at a temperature of 180° C. for 1 hour to produce a conductive elastic layer roller 1 including a conductive elastic layer having a thickness of 2.00 mm on the outer periphery of the substrate.

[0268] Table 3

[0269]

[0270] Preparation of surface coating liquid

[0271] Production of isocyanate-terminated prepolymer B-1

[0272] In a nitrogen atmosphere, in a reaction vessel, 100 parts by mass of a polyether polyol (trade name: PTG-L3500, produced by Hodogaya Chemical Co., Ltd.) was gradually added dropwise to 25 parts by mass of polymeric MDI (trade name: MILLIONATEMR200, produced by NIPPON POLYURETHANE INDUSTRY CO., LTD.). At this time, the temperature in the reaction vessel was maintained at 65°C. After the dropwise addition was completed, the reaction was carried out at 65°C for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer B-1 having an isocyanate group content of 4.3% by mass.

[0273] Preparation of surface coating liquid

[0274] Next, the raw materials were mixed in the proportions described in Table 4 below.

[0275] Table 4

[0276]

[0277] Subsequently, a mixed solution 1 was obtained by adding methyl ethyl ketone (MEK) so that the solid content in the above raw materials became 30% by mass. In addition, 1,250 parts by mass of the mixed solution and 200 parts by mass of glass beads having an average particle size of 0.8 mm were put into a glass bottle having an internal volume of 450 mL, and dispersed for 3 hours by using PAINT SHAKER (produced by Toyo Seiki Seisaku-sho, Ltd.). Thereafter, the glass beads were removed to obtain a coating solution for surface layer formation.

[0278] Production of developer rollers

[0279] The conductive elastic layer roller 1 was dipped into the coating liquid once and air-dried at 23° C. for 30 minutes. Subsequently, drying was performed in a hot air circulation dryer set at 160° C. for 1 hour to produce a developing roller 1 in which a surface layer was formed on the outer peripheral surface of the conductive elastic roller. In this regard, the dipping time during the dip coating was 9 seconds. The pulling time during the dip coating was adjusted so that the initial speed was set to 20 mm / s, the final speed was set to 2 mm / s, and the speed was linearly changed between 20 mm / s and 2 mm / s with time.

[0280] Image evaluation

[0281] For image forming devices, use Figure 1 A modification machine and modification box of a tandem system laser beam printer HP ColorLaser Jet Enterprise CP4525dn (produced by Hewlett-Packard Company) having the configuration shown in FIG. Figure 1 , reference numeral 11 denotes a photosensitive member, reference numeral 12 denotes a developing roller, reference numeral 13 denotes a colorant supplying roller, reference numeral 14 denotes a colorant, reference numeral 15 denotes a regulating member, reference numeral 16 denotes a developing device, reference numeral 17 denotes a laser, reference numeral 18 denotes a charging device, reference numeral 19 denotes a cleaning device, reference numeral 20 denotes a charging device for cleaning, reference numeral 21 denotes a stirring blade, reference numeral 22 denotes a driving roller, reference numeral 23 denotes a transfer roller, reference numeral 24 denotes a bias power source, reference numeral 25 denotes a tensioning roller, reference numeral 26 denotes a transfer conveying belt, reference numeral 27 denotes a driven roller, reference numeral 28 denotes paper, reference numeral 29 denotes a supplying roller, reference numeral 30 denotes an attraction roller, and reference numeral 31 denotes a fixing device.

[0282] The remodeling machine was remodeled to set the process speed to 320 mm / s by changing the internal gear. In addition, the product toner was taken out from the inside of the box, cleaned by blowing, the developing roller was changed to the produced developing roller 1, and 250 g of toner 1 was filled. The resulting toner box was left in an environment of 30° C. and 80% RH for 24 hours, and installed on the black station of the printer. The box was installed on other stations, and an image output test was performed.

[0283] For image evaluation, 25,000 images were output while repeating the following operation: two images with a printing rate of 1% were printed and then printing was paused for 1 minute, the machine was left in an environment with a temperature of 30° C. and a humidity of 80% RH for 14 days, and then the following horizontal streak evaluation was performed.

[0284] After the evaluation, 50,000 images were further outputted while repeating the following operation: printing two images with a printing rate of 1% and then pausing printing for 1 minute, the machine was left in an environment of 30° C. and 80% RH for 14 days, and thereafter the following horizontal streak evaluation was performed.

[0285] Evaluation of horizontal streaks after 14 days in an environment with a temperature of 30°C and a humidity of 80% RH

[0286] After outputting 25,000 or 50,000 images, the machine was left in an environment of 30°C and 80%RH for 14 days, and halftone images were output to evaluate the occurrence of horizontal white streak-like images and horizontal black streak-like images. The evaluation criteria are as follows.

[0287] A: No horizontal streak-like defects were observed.

[0288] B: Horizontal streak-like defects are hardly observed.

[0289] C: The occurrence of horizontal streak-like defects was observed in some areas corresponding to the rotation pitch of the developing roller, but there was no problem in practical use.

[0290] D: A horizontal streak-like defect is observed in a wide area, and the horizontal streak-like defect is conspicuous.

[0291] Production Examples of Toners 2 to 20

[0292] Toners 2 to 20 were produced in the same manner as in Production Example of Toner 1, except that the production conditions and formulation described in Table 1 were adopted. Table 2 describes the physical properties of Toners 2 to 18. The production method of each raw material will be described below.

[0293] The physical properties of the obtained Toner 19 are shown in Table 5.

[0294] Likewise, for Toner 20, it was confirmed that no external additive having a major diameter of 40 nm or more and 400 nm or less was present. The physical properties of the obtained Toner 20 are shown in Table 6.

[0295] Production Examples of Silica Particles 2 to 4

[0296] Silica particles 2 to 4 were obtained as described below. The amount of methanol used in the production example of silica particles 1 was changed to 634.0 g, 842.1 g, and 883.5 g, respectively. The dropping time of tetramethoxysilane was changed to 7 hours, 6 hours, and 5 hours, respectively, and the dropping time of 5.4% by mass ammonia water was changed to 6 hours, 5 hours, and 4 hours, respectively. The major diameter of the silica particles was adjusted by such operations. In addition, when the surface treatment was performed with HMDS so that the carbon amount became equal to the amount in silica particles 1, the amount of HMDS and water was adjusted.

[0297] Production Example of Silica Granules 5

[0298] Silica particles 5 were obtained as follows. The amount of methanol used in the production example of silica particles 1 was changed to 382.7 g. The amount of 28% by mass ammonia water was changed to 37.1 g. The dropping time of tetramethoxysilane was changed to 7 hours, and the dropping time of 5.4% by mass ammonia water was changed to 6 hours. The major diameter of the silica particles was adjusted by such operations. In addition, when the surface treatment was performed with HMDS so that the amount of carbon became equal to that in silica particles 1, the amounts of HMDS and water were adjusted.

[0299] Production Example of Silica Granules 6

[0300] Silica particles 6 were obtained as follows. The amount of methanol used in the production example of silica particles 1 was changed to 491.3 g. The dropping time of tetramethoxysilane was changed to 7 hours, and the dropping time of 5.4% by mass ammonia water was changed to 6 hours. The major diameter of the silica particles was adjusted by such operations. In addition, when the surface treatment was performed with HMDS so that the carbon amount became equal to that in silica particles 1, the amounts of HMDS and water were adjusted.

[0301] Production Examples of Silica Granules 7 and 8

[0302] Silica particles 7 and 8 were obtained as follows. The amount of methanol used in the production example of silica particles 1 was changed to 405.5 g and 385.5 g, respectively. The dropping time of tetramethoxysilane was changed to 7 hours, and the dropping time of 5.4% by mass ammonia water was changed to 6 hours. The major diameter of the silica particles was adjusted by such operations. In addition, when the surface treatment was performed with HMDS so that the carbon amount became equal to the amount in silica particles 1, the amounts of HMDS and water were adjusted.

[0303] Production Example of Silica Granules 10

[0304] By using 100 parts of dry silica fine powder (BET specific surface area of ​​90 m 2 / g) was treated with 15 parts of hexamethyldisilazane (HMDS) and 15 parts of dimethyl silicone oil for hydrophobization.

[0305] Table 5

[0306]

[0307] Table 6

[0308]

[0309] Production Example of Developing Rollers 2 to 18

[0310] Developing rollers 2 to 18 were produced in the same manner as for developing roller 1, except that the compositions of the conductive elastic layer roller and the surface layer coating liquid were set as described in Table 7. Here, the raw materials described in Table 7 are shown in Table 8, and the production method of each raw material will be described below. The physical properties of developing rollers 2 to 16 are described in Table 9.

[0311] As a result of measuring the elastic coefficient of resin particles of the rubber slice of the surface layer in the thickness direction, it was confirmed that no resin particles having an elastic coefficient of 100 MPa or more and 10,000 MPa or less were present for the developing roller 17. The physical properties of the developing roller 17 are described in Table 10.

[0312] For the developing roller 18, as a result of measuring the elastic coefficient of the resin particles of the rubber slices of the surface layer in the thickness direction, it was confirmed that there were no resin particles having an elastic coefficient of 2 MPa or more and 50 MPa or less.

[0313] Table 7

[0314]

[0315] Table 8

[0316]

[0317] Preparation of surface coating liquid

[0318] Production of Isocyanate-Terminated Prepolymer B-2

[0319] In a nitrogen atmosphere, in a reaction container, 100 parts by mass of polycarbonate polyol (trade name: DURANOLT5652, produced by Asahi Kasei Corporation) was gradually added dropwise to 33 parts by mass of polymeric MDI (trade name: MILLIONATE MR200, produced by NIPPON POLYURETHANE INDUSTRY CO., LTD.). At this time, the temperature in the reaction container was maintained at 65°C. After the dropwise addition was completed, the reaction was carried out at 65°C for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer B-2 having an isocyanate group content of 4.3% by mass.

[0320] Production of Urethane Granules D-2

[0321] A suspension is formed by adding 3 parts by mass of amine polyol A-3 and 97 parts by mass of isocyanate-terminated prepolymer B-1 to water containing a suspension stabilizer (calcium phosphate) and stirring. Subsequently, the suspension is heated to start the reaction, and the reaction is fully carried out to generate carbamate particles. Thereafter, the carbamate particles are recovered by solid-liquid separation, the suspension stabilizer is removed by washing, and dried. The resulting carbamate particles are classified by using an air classifier (trade name: Model EJ-L-3, produced by Nittetsu Mining Co., Ltd.). The result of measuring the volume average particle diameter (median diameter) of the carbamate particles using a particle size distribution analyzer (trade name: Coulter Multisizer II, produced by Beckman Coulter, Inc.) is 13.0 μm. It is used as carbamate particles D-2.

[0322] Production of urethane granules D-3, D-9, and D-10

[0323] Carbamate particles D-3 (volume average particle diameter: 20.0 μm), carbamate particles D-9 (volume average particle diameter: 8.0 μm), and carbamate particles D-10 (volume average particle diameter: 30.0 μm) were produced in the same manner as the production of carbamate particles D-2, except that the stirring speed of the suspension and the classification conditions of the carbamate particles were changed.

[0324] Production of Urethane Granules D-5

[0325] Urethane particles ART PEARL U400 clear (trade name, average particle size 15.1 μm, produced by Negamichemical industrial co., ltd.) were classified by using an air classifier (trade name: Model EJ-L-3, produced by Nittetsu Mining Co., Ltd.). The volume average particle size (median diameter) of the urethane particles was measured by using a particle size distribution analyzer (trade name: Coulter Multisizer II, produced by Beckman Coulter, Inc.) and the result was 13.0 μm. This was designated as urethane particles D-5.

[0326] Production of Urethane Granules E-6 and E-7

[0327] Urethane particles E-6 (volume average particle diameter: 8.0 μm) and urethane particles E-7 (volume average particle diameter: 8.0 μm) were produced in the same manner as in the production of urethane particles D-2, except that the polyol was changed to 35 parts by mass of the polycarbonate polyol A-2, the isocyanate was changed to 65 parts by mass of the isocyanate-terminated prepolymer B-2, and the stirring speed of the suspension and the classification conditions of the urethane particles were changed.

[0328] Table 9

[0329]

[0330] Table 10

[0331]

[0332] Table 11

[0333]

[0334] Examples 2 to 25 and Comparative Examples 1 to 10

[0335] Image evaluation similar to that of Example 1 was performed by using the toners 1 to 21 and the developing rollers 1 to 18 in combination as described in Table 8. The evaluation results are described in Table 12.

[0336] Table 12

[0337]

[0338] According to the present disclosure, there is provided a process cartridge capable of producing high-quality images even when the speed is increased, even when the service life is increased, and even after being left for a long period of time during use of the process cartridge in a high-temperature and high-humidity environment.

[0339] While the present disclosure has been described with reference to exemplary embodiments, it is to be understood that the present disclosure is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A process cartridge detachably mounted to a main body of an electrophotographic device, the process cartridge comprising: Toner; Developing roller; and Adjustment components, Characterized in that the developing roller comprises: Conductive substrate, an elastic layer on the conductive substrate, and a surface layer on the elastic layer, The surface layer comprises: Binder resin, first resin particles, and second resin particles, The surface layer has an outer surface, and the outer surface has: first bulge, and a second convex portion existing in a region excluding the first convex portion and having a height lower than that of the first convex portion by 5.0 μm or more, The first protrusions are derived from the first resin particles, The second protrusions are derived from the second resin particles, the first resin particles have an elastic modulus of 100 MPa or more and 10,000 MPa or less, the elastic modulus of the first resin particles being measured in a cross section in a thickness direction of the surface layer, The elastic modulus of the second resin particles is 2 MPa or more and 50 MPa or less, the elastic modulus of the second resin particles being measured in a cross section in a thickness direction of the surface layer, The average value of the maximum height Rz of the outer surface is 6 μm or more and 18 μm or less, The toner includes: Toner particles, and an external additive A dispersed on the surface of the toner particles and covering the surface of the toner particles, The external additive A is a silica particle having a long diameter of 40 nm or more and 400 nm or less, The coverage of the surface of the toner particles by the external additive A is 3.0% or more, and The external additive A has a dispersion evaluation index D of 2.0 or less. 2 . The process cartridge according to claim 1 , wherein a dispersion evaluation index D of the external additive A is 0.5 or more and 1.20 or less.

3. A process cartridge according to claim 1 or claim 2, wherein the toner further comprises an external additive B covering the surface of the toner particles, The external additive B is a silica particle having a major diameter of 5 nm or more and less than 40 nm, and The coverage of the surface of the toner particles by the external additive B is 62% or more and 100% or less.

4. A process cartridge according to claim 3, wherein The external additive A and the external additive B are fixed to the toner particles, and The total adhesion rate of the external additive A and the external additive B is 70% or more.

5. A process cartridge according to claim 1 or claim 2, wherein the volume average diameter D1 of the first resin particles, the volume average diameter D2 of the second resin particles, and the volume average diameter Dt of the toner satisfy the relationship represented by the following formula (a): (D1-D2)-Dt>0 (a).

6. A process cartridge according to claim 1 or claim 2, wherein the volume average diameter D2 of the second resin particles and the average major diameter Da of the external additive A satisfy the relationship represented by the following formula (b): D2 / Da≤40 (b).